Acute Effect of Front Crawl Sprint Resisted Swimming on the Propulsive Forces of the Hand - Gourgoulis, V.; Aggeloussis, N.; Mavridis, G.; Boli, A.; Kasimatis, P.; Vezos, N.; Toubekis, A. G.; Antoniou, P.; Mavrommatis, G. (Journal of Applied Biomechanics, 2013)
The purpose of the current study was to investigate the acute effect of sprint resisted front crawl swimming on the propulsive forces of the hand. Eight female swimmers swam 25 m with maximal intensity, with and without added resistance. A bowl with a capacity of 2.2, 4 and 6 L was used as low, moderate and high added resistance, respectively. The underwater motion of the swimmer`s right hand was recorded using 4 cameras (60 Hz) and the digitization was undertaken using the Ariel Performance Analysis System. Repeated-measures ANOVA revealed that the velocity of the hand, the pitch and the sweepback angles of the hand, as well as the magnitude and the relative contribution of the drag and lift forces were not significantly modified and thus the magnitude of the resultant force did not change. Moreover, the magnitude of the effective force, as well as the angle formed between the resultant force and the axis of the swimming propulsion were not significantly affected. Thus, it could be concluded that resistance added as in this study did not alter the pattern of the propulsive hand forces associated with front crawl sprinting.